2011
DOI: 10.5194/tcd-5-755-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in seasonal snow cover in Hindu Kush-Himalayan region

Abstract: The changes in seasonal snow covered area in the Hindu Kush-Himalayan (HKH) region have been examined using Moderate – resolution Imaging Spectroradiometer (MODIS) 8-day standard snow products. The average snow covered area of the HKH region based on satellite data from 2000 to 2010 is 0.76 million km<sup>2</sup> which is 18.23% of the total geographical area of the region. The linear trend in annual snow cover from 2000 to 2010 is &minus;1.25&plusmn;1.13%. This is in consistent with earlie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…Permanent snow/ice covered land and unused land were also amongst the LULC types that were more on the decline. This is in consistent with previous studies at regional and national scales [74,75]. The decreasing and increasing rates of snow/ice covered land were 1.5% and 1.3%, respectively.…”
Section: Land Use Change Magnitudesupporting
confidence: 81%
See 1 more Smart Citation
“…Permanent snow/ice covered land and unused land were also amongst the LULC types that were more on the decline. This is in consistent with previous studies at regional and national scales [74,75]. The decreasing and increasing rates of snow/ice covered land were 1.5% and 1.3%, respectively.…”
Section: Land Use Change Magnitudesupporting
confidence: 81%
“…There was an increase in water bodies of 1,272,013 ha (55% of 2010) against a On the other hand, the rate of decrease of forest areas (i.e., 5.8%) was about three times higher than the rate of increase (i.e., 1.6%), resulting in a decline of forest covers. The previous studies on Afghanistan's forest change also confirm the rapid rate of forest cover decrease [72][73][74]. Use of wood for fuel and heating, illegal smuggling, instability in the forest-dominant areas, weak management, and urban and cropland expansion were considered to be the main drivers of deforestation [39,71,73].…”
Section: Land Use Change Magnitudementioning
confidence: 97%
“…Some studies (e.g. Gafurov and Bardossy, 2009;Gurung et al, 2011) applied different techniques for filtering cloud obscured pixels from the MODIS snow cover products. In this study, we observed that the percentage of cloud covers and its timing varies significantly at different elevation zones.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the accurate characterisation of absorbing aerosols and spectral surface albedo is essential in understanding the regional heterogeneity of aerosol DRFs at TOA. As the annual mean snow cover accounts for only 18% of the total geographical area of the Himalayas (Gurung et al, 2011), the large heterogeneities in the surface albedos are very important in the estimation of regional climate forcings. A precise analysis of snow cover seasonality is also essential for a better understanding of the DRF over the Himalayan region.…”
Section: Wet Deposition and Snowfall Eventsmentioning
confidence: 99%